Prevalence of parasites in fish from the pelagic and benthic zones - Kamaludeen, Juriah; Hassan, Mohammad Nasir; Malahubban, Masnindah; Latif, Kamil; Yu Abit, Lirong; Syed Hussain, Sharifah Salmah; Mustafa, Suhaili; Mohamad, Nora Faten Afifah; Mohammad Ali Hanafiah, Muhammad Hakim; Bura Thlama, Paul; Pertiwi, Herinda; A. Altwaim, Sarah (Persatuan Biologi Gunaan Malaysia, 2023)
The present research is a comparative study on the prevalence of parasites in marine finfish among the two major marine zones; namely the pelagic zone and benthic zone. The objectives of the present study were to investigate the parasite prevalence in both zones, as well as to determine the effect of differing marine zones regarding the presence of parasites in fish. A total of 30 individual fish occurring in pelagic and benthic zones were randomly selected from three different fishmongers at a wet market in Bintulu, Sarawak. Both the gill and stomach content of the samples were examined to detect the presence of parasites. Nematodes and trematodes were observed in the intestinal tract of the fish, Cymothoa exigua was found attached to the fish tongue, and monogenean parasites were also detected on the gills. The prevalence of the parasite was roughly equal in Setipinna breviceps, Ilisha megaloptera, and Selaroides leptolepis. The highest prevalence of parasites (87.50%) from fish in the benthic zone based on fish size was for fish measuring between 20.1 - 30.00 cm in total length (P-value=0.3778), whereas for pelagic fish, the highest prevalence of parasites (100%) in fish measurements of 30.1 – 40.0 cm in total length (P-value=0.0044).  A major factor for the diversity of marine fish parasites occurring in the different zones is the difference in feeding behavior of the hosts and depth distribution which resulted in low or high rates of parasite infestation.